Blue space geographies: Enabling health in place. (September 2015) - Foley, Ronan; Kistemann, Thomas
Abstract: Drawing from research on therapeutic landscapes and relationships between environment, health and wellbeing, we propose the idea of 'healthy blue space' as an important new development Complementing research on healthy green space, blue space is defined as; 'health-enabling places and spaces, where water is at the centre of a range of environments with identifiable potential for the promotion of human wellbeing'. Using theoretical ideas from emotional and relational geographies and critical understandings of salutogenesis, the value of blue space to health and wellbeing is recognised and evaluated. Six individual papers from five different countries consider how health can be enabled in mixed blue space settings. Four sub-themes; embodiment, inter-subjectivity, activity and meaning, document multiple experiences within a range of healthy blue spaces. Finally, we suggest a considerable research agenda – theoretical, methodological and applied – for future work within different forms of blue space. All are suggested as having public health policy relevance in social and public space.